Penerapan Metode Dempster Shafer pada Sistem Pakar Diagnosa Penyakit Lambung Berbasis Web di Puskesmas Wallandimu - Stefani Natalia Kaka Daha; Andreas Ariyanto Rangga; Katarina Yunita Riti (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Gastric disease is a common health problem that can disrupt daily activities if not properly treated. To aid the initial diagnosis process, this study developed a web-based expert system capable of diagnosing various types of gastric disease based on the symptoms experienced by the user. This system uses the Dempster-Shafer method to address uncertainty in decision-making by combining a number of pieces of evidence in the form of symptoms to determine the level of confidence in a disease. The system was developed using the PHP programming language and a MySQL database and designed for easy browser access. Testing demonstrated that the system was able to provide fairly accurate diagnostic results that closely approximated the results of consultations with medical professionals. This system is expected to become an initial solution for the public in quickly and independently recognizing symptoms of gastric disease.